Editorial - Viáfara González, John Jairo (Universidad Pedagógica y Tecnológica de Colombia, 2016)
Recently COLCIENCIAS, the governmental agency for the promotion of science and technology in Colombia, has shared its new policy for what they claim would be an improvement to the quality of national scientific journals and a new model to classify scientific national publications. The new model and policies are basically the adoption of international standards to evaluate and measure Colombian scientific journals. As the editor of ENLETAWA journal, I would like to start this editorial by expressing my concern regarding the future of many Colombian journals which have tried, as in the case of our ublication, to become a space for the dissemination of academic work produced by individuals in our field. Our journal has been working for years to adopt COLCIENCIAS guidelines in order to gain thisagency´s recognition as a quality publication. Unfortunately the adoption of new policies and standards, which are not grounded in the specific characteristics of the Colombian context and which deepen the imposition of models privileging and legitimizing the value of exact and applied sciences over human sciences, cannot been regarded as a measure designed to improve journals in the humanities.